Labour promotes systemic mobilisation of monocytes, T cell activation and local secretion of chemotactic factors in the intervillous space of the placenta - Vikberg, Sara; Lindau, Robert; Solders, Martin; Raffetseder, Johanna; Budhwar, Snehil; Ernerudh, Jan; Tiblad, Eleonor; Kaipe, Helen (Frontiers in Immunology, 2023)
During pregnancy, maternal blood circulates through the intervillous space of the placenta and the reciprocal interactions between foetal tissues and maternal immune cells makes the intervillous space a unique immunological niche. Labour is characterised by a proinflammatory response in the myometrium, but the relationship between local and systemic changes during the onset of labour remains elusive. We here aimed to investigate how the systemic and intervillous circulatory systems are affected during labour from an immunological point of view. We report that the proportion of monocytes is dramatically higher in peripheral (PB), intervillous blood (IVB) and decidua in labouring (n = 14) compared to non-labouring women (n = 15), suggesting that labour leads to both a systemic and local mobilisation of monocytes. Labour was associated with a relative increase of effector memory T cells in the intervillous space compared to the periphery, and MAIT cells and T cells showed an elevated expression of activation markers both in PB and IVB. Intervillous monocytes consisted to a higher degree of CD14+CD16+ intermediate monocytes compared to peripheral monocytes, independently of mode of delivery, and displayed an altered phenotypic expression pattern. A proximity extension assay analysis of 168 proteins revealed that several proteins associated to myeloid cell migration and function, including CCL2 and M-CSF, were upregulated in IVB plasma in labouring women. Thus, the intervillous space could be a bridging site for the communication between the placenta and the periphery, which contribute to monocyte mobilisation and generation of inflammatory reactions during spontaneous labour.